Settlement of abuse of authority that caused state losses according to indonesian government administration law - Laksito, FX. Hastowo Broto; Bawono, Aji (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
State Financial Losses are the result of acts of misuse of the authority of the state apparatus which have an impact on not maximisingnational development. This problem is also experienced by many countries and seeks to eradicate and minimise such events. Indonesia hasa national regulation, namely Law Number 30 of 2014, there is a growing assumption that in the abuse of authority that causes statelosses and the losses are returned the problem is over. In fact, according to Article 4 of Law Number 31 Year 1999, the return of statelosses does not eliminate criminal liability. This research examines how to resolve abuse of authority that harms state finances in theperspective of government administration law and corruption offences. This research is a normative research that uses normative andphilosophical juridical analysis methods. The results of the study found that the return of state losses does not erase the criminal penalty.The perpetrator must still be held criminally responsible for his actions. Administrative examination files are used as evidence in criminalcases. In addition, the internal supervisory institution formed from the Government Administration Law which has the function ofsupervising abuse of authority must coordinate with law enforcement agencies to enforce the law in eradicating acts that result in statefinancial losses.Keywords: Abuse of Authority; State Loss; State Finance